The metabolism of fatty acids and insulin secretion in children with type 1 diabetes mellitus and its complications - N. P. Mikaelyan; A. V. Shestopalov; A. V. Mikaelyan; A. E. Gurina; V. V. Smirnov (Лечащий Врач, 2021)
The study of the state of carbohydrate and lipid metabolism in 47 children and adolescents with type 1 diabetes mellitus showed a progressive decrease in residual insulin secretion and insulin-binding activity of lymphocytes against the background of metabolic disorders of fatty acids, which are risk factors for severe course of the disease with the rapid development of hypoxia and other diabetic complications, including functional disorders in the digestive system.